Mencegah Kecurangan dalam Transaksi Online dengan mengadaptasikan Konsep Siri dan Pacce - Amiruddin, Muhammad Majdy; Ilham, Muhammad; Arief, Muhammad; Hasanuddin, Hasanuddin; Haq, Islamul; Syatar, Abdul (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2019)
The Purpose of this study is conducting mitigate fraud transaction by adapting the concept of siri’ na pacce’. This research is a qualitative research with a critical ethnographic approach. The source of data from this study is primary data in the form of direct interviews to several informants and subjects in the form of data from the research location. Furthermore, the data collection methods used was in-depth interviews, documentation and recording. Then, the processing and data analysis techniques are qualitative analysis by building conclusions with the stages of data collection, triangulation data analysis and final conclusion. The results of this study indicate Lempu’ and ada tongeng 'in the dimension of honesty accountability, namely honesty and wisdom which are keys in reducing fraud. The value of clay is reinforcement in the implementation of accountability can be seen in the process of offering, ordering, payment and delivery.